2018
DOI: 10.5604/01.3001.0011.6803
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mechanical properties of poly (methyl methacrylate) reinforced with glass fibers

Abstract: Introduction. Acrylic resin is a basic material used in preparation of partial and complete dentures. One of the methods of improving mechanical properties of removable dentures is reinforcing acrylic resin with artificial fibers. Aim of the study. To compare mechanical properties of acrylic material reinforced with various types of glass fibers. Material and method. Heat-cured Estetic acrylic resin by Wiedent was used for denture bases. Glass mat, fiberglass fabric, long glass fibers and short glass fibers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Vallittu et al [14][15][16] demonstrated in their numerous researches that the reinforcement of the palatal plate using a single glass fiber layer causes strength increase by 5 %. Our earlier tests also confirmed small strength improvement, as a result of the use of glass fibers [10].…”
Section: Ocena Wytrzymałości Mechanicznej Poli(metakrylanu Metylu) Wzsupporting
confidence: 78%
See 2 more Smart Citations
“…Vallittu et al [14][15][16] demonstrated in their numerous researches that the reinforcement of the palatal plate using a single glass fiber layer causes strength increase by 5 %. Our earlier tests also confirmed small strength improvement, as a result of the use of glass fibers [10].…”
Section: Ocena Wytrzymałości Mechanicznej Poli(metakrylanu Metylu) Wzsupporting
confidence: 78%
“…There are nume rous forms of glass fibers that are used as reinforcement of acrylic plates of removable dentures, however, as demonstrated in our earlier tests, the best strength para meters were achieved with the use of long fibers [10]. The results of the acrylic compound reinforcement method using glass fibers were positive in numerous tests [9][10][11][12][13]. Vallittu et al [14][15][16] demonstrated in their numerous researches that the reinforcement of the palatal plate using a single glass fiber layer causes strength increase by 5 %.…”
Section: Ocena Wytrzymałości Mechanicznej Poli(metakrylanu Metylu) Wzmentioning
confidence: 62%
See 1 more Smart Citation
“…This proves that two effects caused by the presence of fi bers are "competing": the reinforcing effect of carrying loads through the fi bers and the weakening (in the case of compression) of the above-mentioned effect of the structure orientation. Instability of the compressive mechanical properties for composites containing chopped glass fi bers is common (49,50).…”
Section: Badania Właściwości Mechanicznychmentioning
confidence: 99%